A cortina de luz como principal sistema de segurança nas zonas de prensagem em prensas mecânicas - Tamaliunas, Paulo (Universidade do Vale do Rio dos Sinos, 2016)
This article aims to study the use of light curtain as a safety system in pressing zones on mechanical presses. Normative provisions, manufacturers' recommendations and the perception of a group of workers about the safety provided by this system were addressed. A case study was set up and for this purpose a questionnaire was developed with the intention of knowing the study group, their qualification to operate presses and their perception of the existence of risk in this activity. The research group showed a good level of awareness about the risks, and even preferring a configuration with physical elements for protection, they believe in light curtain technology.
Keywords: Cortina de luz; Sistemas de segurança; Zona de prensagem; Percepção de risco; Light curtain; Safety systems; Pressing zone; Perception of risk